Replay : a new book - Creech, Sharon (New York : Joanna Cotler Books, 2005)
While preparing for a role in the school play, twelve-year-old Leo finds an autobiography that his father wrote as a teenager and ponders the ways people change as they grow up. Includes the text for the play, "Rumpopo's Porch."
At head of title: Joanna Cotler Books presents.
Keywords: Conduct of life -- Fiction; Family life -- Fiction; Fathers and sons -- Fiction; Theater -- Fiction; Schools -- Fiction